TINJAUAN PENGGUNAAN KONTEN MEDIA SOSIAL SEBAGAI MEDIA INFORMASI DAN PUBLIKASI KEGIATAN HIPMA AD-DA’WAH BANDUNG - Donny Heryadi (SECAD, 2025)
This journal article is entitled "A Review of the Use of Social Media Content for Publicizing the Activities of HIPMA (Ad-Da'wah Mosque Youth Association) Bandung." It was written by Donny Heryadi. This study aims to examine the use of social media content to increase the effectiveness of social media in conveying information about positive activities of youth at the Ad-Da'wah Mosque in Bandung. The author describes the results of observations and analyzes data obtained in the field through the distribution of questionnaires to obtain responses regarding the use of social media content by HIPMA Ad-Da'wah in Bandung. The results show that the use of technology such as the Instagram application facilitates the dissemination of information to the congregation of the Ad-Da'wah Mosque and the community and encourages increased community participation in Ad-Da'wah Mosque activities.